Differences between Goldmann Applanation Tonometry and Dynamic Contour Tonometry following Trabeculectomy - Efstathios T. Detorakis; Emilia Grammenandi; Ioannis G. Pallikaris; Miltiadis K. Tsilimbaris (Journal of Ophthalmology)
Background. To evaluate differences between Goldmann Applanation Tonometry (GAT) and Dynamic Controur Tonometry (DCT) following trabeculectomy. Methods. Thirty eight glaucomatous eyes with a history of trabeculectomy (Trabeculectomy group, TG), 20 eyes without a history of trabeculectomy but with a history of latanoprost use (Latanoprost group, LG), and 19 nonglaucomatous eyes (Control group, CG) were included. GAT-IOP, DCT-IOP, the difference between them (dIOP), the central corneal thickness (CCT), the axial length (AL), and the depth of the anterior chamber (ACD) were measured. Results. dIOP was significantly higher in TG (5.19 mmHg) than in LG (4.01 mmHg) and CG (1.98 mmHg). Correlations between AL and dIOP were statistically significant in both TG and LG but not in CG whereas correlations between dIOP and other clinical parameters examined were statistically not significant in all groups. Conclusions. The significantly higher dIOP in TG implies that the bio-mechanical properties of the ocular walls are altered following trabeculectomy.